The effect of lavender essential oil on performance, carcass characteristics and serum parameters of broilers - Çolak, A; Yıldız, A (Journal of the Hellenic Veterinary Medical Society, 2024)
This study was carried out to investigate the effect of lavender (Lavandula angustifolia) essential oil addition to broiler diets at different levels on performance, carcass, and blood parameters. A 6-week experiment, 300 unsexed day-old broiler (Ross 308) was used in the experiment. Six treatments consisting of different lavender essential oil levels (0, 50, 100, 150, 200, and 250 %) were used with five replicates of fifty chicks each treatment. Body weight, body weight gain, and feed conversion ratio were linearly affected, and these parameters were improved by the addition of lavender essential oil to the diet (P<0.05). However, feed intake was not affected by the supplementation of lavender essential oil (P>0.05). The effect of lavender essential oil on carcass properties was insignificant (P>0.05). The addition of lavender essential oil to the diet linearly decreased LDL, triglyceride, and albumin levels of serum, whereas total protein level of serum linearly increased in broilers. As a result, it can be said that the addition of 250 mg/kg level of lavender essential oil to the diet is beneficial in improving the performance and serum parameters of broilers.